Synthesis of allahabadolactone A - Wang, Kongchen (2019)
A synthesis of allahabadolactone A is described employing diastereoselective Diels–Alder and selenocyclization reactions, starting from (R)-citronellal and propylene oxide. The Diels–Alder substrate is built up in an efficient manner by rhodium-catalyzed alkyne hydroboration and palladium-catalyzed coupling reactions of E-1,2-dichloroethene. It is observed that the Diels–Alder reaction only displays high diastereoselectivity when the diene bears an additional alkene substituent but not an alkyne substituent.